COVID-19 pandemic in the United States. Issue 4 (December 2020) - Bergquist, Savannah; Otten, Thomas; Sarich, Nick
Highlights: COVID-19 data collection, reporting, and infection has varied widely across states. US policy response has been decentralized with state-specific containment and exit measures. Testing and surveillance have been limited and impeded by unclear federal policies. Abstract: Objectives: The paper highlights US health policy and technology responses to the COVID-19 pandemic from January 1, 2020 – August 9, 2020. Methods: A review of primary data sources in the US was conducted. The data were summarized to describe national and state-level trends in the spread of COVID-19 and in policy and technology solutions. Results: COVID-19 cases and deaths initially peaked in late March and April, but after a brief reduction in June cases and deaths began rising again during July and continued to climb into early August. The US policy response is best characterized by its federalist, decentralized nature. The national government has led in terms of economic and fiscal response, increasing funding for scientific research into testing, treatment, and vaccines, and in creating more favorable regulations for the use of telemedicine. State governments have been responsible for many of the containment, testing, and treatment responses, often with little federal government support. Policies that favor economic re-opening are often followed by increases in state-level case numbers, which are then followed by stricter containment measures, such as mask wearing or pausing re-opening plans. Conclusions: While all US states have begun to "re-open" economic activities, this trend appears to be largely driven by social tensions and economic motivations rather than an ability to effectively test and surveil populations.